การปรับปรุงการประมาณค่าการแจกแจงทวินามปัวซงด้วยการแจกแจงทวินาม - ณพล กาญจโนปถัมภ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
A Poisson binomial random variable is the sum of the independent Bernoulli random variables that are not necessarily identical. The probability of a Poisson binomial random variable cannot be easily calculated. Therefore, we estimate the probability of a Poisson binomial random variable by the probability of a binomial random variable. This is because a binomial random variable is known as the sum of independent and identically distributed Bernoulli random variables and its probability is in an easier form to use. In this work, we revise the probability estimation of a Poisson binomial random variable by a binomial random variable from Ehm (1990). We also compared the results with Neammanee (2003).